Tension Characteristics Analysis of Scraper Chain of Heavy-Duty Scraper Conveyor with Time-Varying Loads - Shuai Li; Zhencai Zhu; Hao Lu; Yujun Xue (Shock and Vibration)
With the intensification and large scale of coal mining, scraper conveyors are developing towards high power, large volume, long haul distance, and high reliability. It is more and more important to obtain the dynamic tension of the scraper chain with time-varying loads. The purpose of this paper is to obtain the dynamic tension of scraper chains of the scraper conveyor with time-varying loads. First, according to the structural characteristics and working environment of the scraper conveyor and the polygon effect of the sprocket, the scraper conveyor dynamic model under the action of the time-varying loads is established by the finite unit method. Second, the load variation rule of the bearing section is explored when the scraper conveyor and shearer work together. Furthermore, the element resistance of each discrete element, the stiffness coefficient of the scraper chain, and the influence of polygonal effect of sprocket wheel are analyzed. And then, the dynamic tension of the scraper chain is obtained by the Hilber–Hughes–Taylor (HHT) method. Finally, the validity of the scraper conveyor dynamic model is verified by the example analysis and field measurement experiment. Due to the influence of heavy starting, the maximum tension of the scraper chain during the starting process is 751.6 kN, which is 12.25% higher than the tension with smooth running (669.6 kN). During the startup stage, significant impacts occur on both motors and scraper chains which may lead to damage. To protect these components effectively, control strategies such as “soft start” or no-load start hold crucial engineering significance in achieving reliable operation of the scraper conveyor. The obtained results can provide a theoretical basis for the reliability evaluation and parameter optimization of the scraper conveyor.